Preparation of Nano‐Spherical Cu‐en and Its Catalytic Study on the Performance of Solid Propellant. Issue 11 (20th September 2020) - Song, Naimeng; Liu, Jianchao; Yang, Li; Liu, Pingan
Abstract: This paper mainly describes a nano‐spherical energetic catalyst Cu‐en. The result of particle size distribution shows that the D50 value of Cu‐en is 80.18 nm. The thermal decomposition process of RDX, AP, and NC is improved obviously after mixed with Cu‐en. Among them, the change of AP is the most significant, and its peaks of high‐temperature decomposition and low‐temperature decomposition degenerate into one decomposition peak. The thermal decomposition temperature of NC also decreased from 214.5 °C to 191.6 °C. In the range of 3–9 MPa, Cu‐en can significantly increase the burning rate of HTPB propellant and reduce the pressure exponent n from 0.684 to 0.459. According to the test data results of the CMDB propellant, the nano‐spherical Cu‐en prepared by the spray drying method has a stronger catalytic ability than the micro‐nano Cu‐en prepared by the high‐energy ball milling method. Abstract :